An Older Men with Chronic Kidney Disease : A Family Medicine Approach - Dasa Novita, Khuznita; Aprilia, Nisa; Andarini, Sri (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2024)
Chronic Kidney Disease (CKD) is a significant global health issue, with hypertension being one of its major risk factors. This article explores a comprehensive Family Medicine-based approach to managing a 54-year-old male patient with CKD accompanied by hypertension. Through a holistic strategy, emphasis is placed on blood pressure control, lifestyle modifications, and strengthening the family's role in supporting the patient’s adherence to therapy. This approach aims to enhance the patient's quality of life, prevent further complications, and optimize remaining kidney function. The study underscores the importance of interprofessional collaboration and effective communication between the patient, family, and healthcare providers for successful CKD management within a primary care context.